2022
DOI: 10.1002/jcsm.12987
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year quantitative magnetic resonance imaging and phosphorus magnetic resonance spectroscopy study in lower limb muscle in dysferlinopathy

Abstract: Background Natural history studies in neuromuscular disorders are vital to understand the disease evolution and to find sensitive outcome measures. We performed a longitudinal assessment of quantitative magnetic resonance imaging (MRI) and phosphorus magnetic resonance spectroscopy ( 31 P MRS) outcome measures and evaluated their relationship with function in lower limb skeletal muscle of dysferlinopathy patients. Methods Quantitative MRI/ 31 P MRS data were obtained at 3 T in two different sites in 54 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 40 publications
6
42
1
Order By: Relevance
“…It has been observed that in dysferlinopathy, the T2 H2O does not correlate with baseline functional scores. 25 T2 H2O has been shown to be impacted by high levels of FF (i.e. >60%) as also described in dysferlinopathy.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…It has been observed that in dysferlinopathy, the T2 H2O does not correlate with baseline functional scores. 25 T2 H2O has been shown to be impacted by high levels of FF (i.e. >60%) as also described in dysferlinopathy.…”
Section: Discussionmentioning
confidence: 78%
“…>60%) as also described in dysferlinopathy. 25 The data described in the current study, however, were acquired in exclusively ambulant patients, where FF values were predominantly lower than 60%. This suggests that T2 H2O could be compared across patients at different stages of muscle loss to offer a snapshot of the current level of disease activity.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations